A Resilient Interface for Approximate Data Access - Fabrício Filho, João; Felzmann, Isaias; Azevedo, Rodolfo; Wanner, Lucas (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Approximate memories offer lower energy cost while introducing errors to applications. If such errors affect essential parts of the application, the execution may fail, decreasing outputs quality and energy savings. We present AxRAM, a memory architecture interface for approximate data that allows applications to benefit from energy savings provided by approximate memories, while improving quality of results and failure rates. AxRAM places critical application data into non-approximate memory regions and implements a resilient addressing scheme that reduces invalid data accesses that lead to application crashes. Compared to an unprotected approximate memory, AxRAM reduces 50.97% of application crashes on average. Compared to a system using non-approximate memories, AxRAM reduces energy consumption by 45.36% on average while providing at least 80% output quality.